Distribution and movement of the mangrove gastropod Littoraria angulifera. (5th March 2021) - Reis, Alice; Alves, Andreia Teixeira; Dórea, Antonio; Beneli, Talita Motta; Santos Freitas, Tamires Santana; Barros, Francisco
Abstract: Organisms have different morphological, physiological, or behavioral strategies for dealing with environmental stressors. Gastropods inhabiting coastal environments, such as mangroves, distribute themselves to match their phenotype with prevalent abiotic conditions (e.g., temperature and humidity). As adults and juveniles differ in basic requirements, differences may be expected regarding their distribution. Juveniles of Littorinid gastropods on rocky shores are more susceptible to hydric stress and stay closer than adults to water sources. In Mangroves, it is unclear if gastropod abundance and movement patterns in different ontogenetic phases are distinctively structured, to match such requirements. We hypothesized that in Littoraria angulifera, body length would increase and abundance would decrease from the base of the mangrove's tree towards the top of the tree (vertical gradient) and from shore edge towards the continent in mangrove forests (horizontal gradient). Furthermore, the movement towards the waterline should be stronger in juveniles, while adults were not expected to display such a pattern. We evaluated the size and abundance of L. angulifera along the vertical and horizontal gradients through mensurative and manipulative experiments. Our results show that the abundance of adults and juveniles of L. angulifera decreased with increasing distance from the water's edge of the mangrove. In the horizontal gradient, the spatial distribution of juveniles was narrower than adults while the movement was toward the mangrove edge for both adults and juveniles. In the vertical gradient, adults and juveniles presented similar movement patterns. Future studies should assess the effect of tides in food availability, predation, and desiccation as a drivers of L. angulifera distribution and movement. Graphical abstract: Image 1 Highlights: We tested if adults and juveniles of Littoraria angulifera differ in distribution. No zonation was found, but juveniles presented a more restricted distribution. Adults and juveniles present residual movement for water source when displaced. Mangrove gastropods distribution pattern is distinct from rocky shore gastropods.